1982
DOI: 10.1099/0022-1317-62-1-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequence Anaylysis of an Immediate-Early Gene Region of the Herpes Simplex Virus Type 1 Genome (Map Coordinates 0.950 to 0.978)

Abstract: SUMMARYThe nucleotide sequence of 4 kilobases of DNA from within the short region of the genome of herpes simplex virus type 1 has been determined. This portion of DNA contains the junctions of the terminal and internal inverted repeat sequence components with the unique sequence component and the 5' regions of the genes which encode the Vmw 12, Vmw 68 and Vmw 175 immediate-early polypeptides. The transcription and translation initiation sites of all three genes and the 5' and 3' boundaries of the Vmw 12 and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
125
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 53 publications
4
125
0
Order By: Relevance
“…From the sequence data of Murchie & McGeoch (1982) it can be concluded that any mutation affecting the 1844 base pair BamHI Y fragment 0000-6503 © 1985 SGM et al, 1979). However, the lesion could still reside within the 275 base pairs of the 5" non-coding region of the gene (Murchie & McGeoch, 1982) which are also part of fragment Y. In order to carry out a fine mapping of the mutation in B a m H I Y, both the w.t.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…From the sequence data of Murchie & McGeoch (1982) it can be concluded that any mutation affecting the 1844 base pair BamHI Y fragment 0000-6503 © 1985 SGM et al, 1979). However, the lesion could still reside within the 275 base pairs of the 5" non-coding region of the gene (Murchie & McGeoch, 1982) which are also part of fragment Y. In order to carry out a fine mapping of the mutation in B a m H I Y, both the w.t.…”
mentioning
confidence: 99%
“…Autoradiographs of lanes (a) determined were residues 570 to 713 for the w.t. type and residues 570 to 786 for the mutant; this numeration takes as number 1 the first residue of the presumed translation initiator codon (Murchie & McGeoch, 1982). The sequences presented in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pGX60 contains part of the sequences encoding the immediate-early polypeptide IE 175. This region of HSV DNA is not known to contain control elements (Murchie & McGeoch, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Both are inserted between the BamHl and Sail sites of pAT153 and can be excised using a combination of these two enzymes, pGX60 was produced by inserting BamHI y (1840 bp) into the BamHI site of pAT153 (Stow, 1982). Digestion with HinfI yields a 619 bp fragment (Murchie & McGeoch, 1982). The derivations of plasmids pG3b, pR 10 and pR9 which have a sequence containing fragments have all been described .…”
Section: Methodsmentioning
confidence: 99%